Zasady techniki prawodawczej a akty prawa miejscowego; wybrane problemy w świetle orzecznictwa Naczelnego Sądu Administracyjnego - Jaroszyński, Tomasz (Kwartalnik Prawa Publicznego, 2013)
The Principles of Legislative Technique (PLT), determined in the Regulation of the Prime Minister of June 20, 2002, are the guidelines, which shall be taken into account during the process of adopting enactments of local law. Enactments of local law are universally binding normative acts, adopted by organs of local government and territorial organs of government administration and applicable to their territorially defined areas of operation. This article deals with 4 issues concerning the applicability of PLT to enactments of local law, which are the subject of judicial decisions of the Supreme Administrative Court. As for the obligation of observance of PLT by the authors of enactments of local law, the Supreme Administrative Court does not undermine it, but raises some doubts in this area. The scope of application of PLT to enactments of local law, determined in paragraph 143 of PLT, should be conformed to specific nature of these acts. The ban on repeating statutory provisions in enactments of local law should be respected, however in certain cases „rewriting” some provisions from a statute should be accepted, because it may make the legal act more coherent and readable. Paragraph 32 of PLT raises serious doubts regarding the rule of functioning of the organs of public authorities on the basis of, and within limits of, the law, hence this provision should be amended.